Роль методу проектів як одного з видів нетрадиційного проведення занять з англійської мови - Петровська, Надія Максимівна; Petrovska, N. M.; Судима, Тетяна Михайлівна; Syduma, T. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті підкреслюємо важливість новітніх методів викладання іноземної мови, зокрема використання методу проекту як одного з видів нетрадиційних практичних занять з англійської мови, який виступає засобом розвитку комунікативних навичок учнів загальноосвітніх шкіл та студентів вищих навчальних закладів. Систематизовано й узагальнено теоретичний та практичний матеріал із проблеми, що досліджується, охарактеризовано метод проекту як один з видів нетрадиційного проведення занять, представлено прийоми роботи під час проведення занять за методом проектів. Подано методичні рекомендації використання цього методу. У статті підкреслюємо важливість новітніх методів викладання іноземної мови, зокрема використання проектів як одного з видів презентації «Печа-Куча» як одного з методів. The article deals with the importance of project method as one of non-traditional ways of conducting English lessons. Such lessons form interest to foreign languages and develop creative abilities of pupils / students. The communicative skills are developed at using project method. This method encourages the use of English both outside and inside the classroom. The ways of project method organizing, the advantages that project work presents, different types of projects are described in the given article. When we design different kinds of project work, we try to bear in mind that our pupils / students need to use the language as effectively as possible. Students’ projects require pupils / students to apply their developing language skills to negotiate, solve problems and acquire new information. Both pair and group work allow the students participate actively in discussions or simply creating real-life situations. The great attention is paid to the presentation methodology «Pecha-Kucha» in which twenty slides are shown for twenty second each (six minutes and forty seconds in total).
The Role of Project Method as one of Non-traditional Ways of Conducting English Lessons
Keywords: комунікативні навички; communicative skills; нетрадиційні заняття; non-traditional lessons; презентація; presentation